A prothrombin activator from Bothrops erythromelas (jararaca-da-seca) snake venom: characterization and molecular cloning - Silva, Márcia B. (2003)
A novel prothrombin activator enzyme, which we have named 'berythractivase', was isolated from Bothrops erythromelas (jararaca-da-seca) snake venom. Berythractivase was purified by a single cation-exchange-chromatography step on a Resource S (Amersham Biosciences) column. The overall purification (31-fold) indicates that berythractivase comprises about 5% of the crude venom. It is a single-chain protein with a molecular mass of 78 kDa. SDS/PAGE of prothrombin after activation by berythractivase showed fragment patterns similar to those generated by group A prothrombin activators, which convert prothrombin into meizothrombin, independent of the prothrombinase complex. Chelating agents, such as EDTA and o-phenanthroline, rapidly inhibited the enzymic activity of berythractivase, like a typical metalloproteinase. Human fibrinogen Aα-chain was slowly digested only after longer incubation with berythractivase, and no effect on the β- or γ-chains was observed. Berythractivase was also capable of triggering endothelial proinfiammatory and procoagulant cell responses, von Willebrand factor was released, and the surface expression of both intracellular adhesion molecule-1 and E-selectin was up-regulated by berythractivase in cultured human umbilical-vein endothelial cells. The complete berythractivase cDNA was cloned from a B. erythromelas venom-gland cDNA library. The cDNA sequence possesses 2330 bp and encodes a preproprotein with significant sequence similarity to many other mature metalloproteinases reported from snake venoms. Berythractivase contains metalloproteinase, desintegrin-like and cysteine-rich domains. However, berythractivase did not elicit any haemorrhagic response. These results show that, although the primary structure of berythractivase is related to that of snake-venom haemorrhagic metalloproteinases and functionally similar to group A prothrombin activators, it is a prothrombin activator devoid of haemorrhagic activity. This is a feature not observed for most of the snake venom metalloproteinases, including the group A prothrombin activators.